Sampling protocol to assess occupational exposure to bioburden in clinical facilities - Viegas, Carla (2018)
Bioburden (comprising fungi and bacteria) is associated with a wide range of adverse health effects and besides patients, clinical staff is also at risk to be exposed. Most of the studies worldwide focusing on bioburden for Indoor Air Quality (IAQ) studies or for occupational exposure assessments purposes rely mostly on air sampling (active methods). In Portugal, occupational health concern has been increasing, and efforts have been made to standardize exposure assessment procedures in occupational environments. However, these are currently not adapted to health care facilities. Therefore, a national and international network - EXPOSE Project - of academic institutions, in direct collaboration with public health institutions, developed a project aiming to propose a sampling protocol to access occupational exposure to bioburden in clinical facilities.